Fassier-Duval Telescopic System: How I Do It?. Issue 6 (September 2017) - Fassier, Francois
Abstract : The author describes step-by-step the technique for Fassier-Duval rodding of both femurs and tibiae in osteogenesis imperfecta. Preoperative evaluations and planning, postoperative care and place of bisphosphonates as explained. Emphasis is given on the different tricks to avoid intraoperative problems.